2017
DOI: 10.1093/mnras/stx1148
|View full text |Cite
|
Sign up to set email alerts
|

UVI colour gradients of 0.4 < z < 1.4 star-forming main-sequence galaxies in CANDELS: dust extinction and star formation profiles

Abstract: This paper uses radial colour profiles to infer the distributions of dust, gas and star formation in z = 0.4-1.4 star-forming main sequence galaxies. We start with the standard UVJ -based method to estimate dust extinction and specific star formation rate (sSFR). By replacing J with I band, a new calibration method suitable for use with ACS+WFC3 data is created (i.e. UVI diagram). Using a multi-wavelength multiaperture photometry catalogue based on CANDELS, UVI colour profiles of 1328 galaxies are stacked in s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 99 publications
6
28
0
Order By: Relevance
“…We also find marginal evidence (through a linear fit) that the slope of intra-clump regions' color gradient becomes steeper with galaxy M * at z 1  . This result is consistent with recent studies of the color gradient of integrated light in galaxies, e.g., Liu et al (2016), Tacchella et al (2017), and Wang et al (2017). Figure 8 implies that clumps' color gradient at z 2 < would be changed if the colors were measured by using the fluxes without background subtraction.…”
Section: Radial Variation Of Clump Color (Color Gradient)supporting
confidence: 92%
See 2 more Smart Citations
“…We also find marginal evidence (through a linear fit) that the slope of intra-clump regions' color gradient becomes steeper with galaxy M * at z 1  . This result is consistent with recent studies of the color gradient of integrated light in galaxies, e.g., Liu et al (2016), Tacchella et al (2017), and Wang et al (2017). Figure 8 implies that clumps' color gradient at z 2 < would be changed if the colors were measured by using the fluxes without background subtraction.…”
Section: Radial Variation Of Clump Color (Color Gradient)supporting
confidence: 92%
“…We compare our measurements (brown lines in Figure 10) with those of Wang et al (2017;green dashed lines) and Tacchella et al (2017;purple dashed line). The methods used by Wang et al and Tacchella et al are different from ours.…”
Section: Dust Extinction Gradientsupporting
confidence: 54%
See 1 more Smart Citation
“…For example, Wuyts et al (2011b) shows that galaxies on the main sequence at a fixed stellar mass have a larger size on average at z ∼ 0.1 than at z ∼1. Due to this evolution, and the fact that opacity also varies with radius in galaxies out to at least z < 2 (Tacchella et al 2017;Wang et al 2017), we cannot interpret the slopes of the attenuation-inclination relation reported in this paper in the context of an evolutionary picture for particular galaxies. Instead, we emphasise that the inclination dependence of the UV attenuation in the largest and most massive star-forming disk galaxies at z ∼ 0.7 (which are not necessarily the same galaxies that will end up in our sample at z = 0.07), behaves similarly to that in galaxies selected to have the same stellar mass and radius at z ∼ 0.…”
Section: Evolution Of Disk Opacitymentioning
confidence: 73%
“…It appears that some C-SFB objects have moved up into the green valley, or even merged with the quenched clump using this color. The combination of red g − z plus blue NUV −r could mean dust (e.g., Williams et al 2009;Patel et al 2011;Brammer et al 2011) or composite stellar populations (Wang et al 2017). ∆Σ 1 appears slightly tighter than ∆ µ e in the G09 sample.…”
Section: ∆ µ E and ∆σ 1 Compared To Stellar-population Parametersmentioning
confidence: 88%